THE 1740 RACIAL TRAGEDY AND LOSS OF BATAVIA SUGARCANE INDUSTRIES - Wibowo, Priyanto (History Department, Semarang State University and Historian Society of Indonesia, 2013)
The racial tragedy inÃÂ Batavia inÃÂ 1740 generally has a great social and economic impact in Java.ÃÂ Chinese people, some of whom were the sugar industry owners possessing the links from the raw materials to finished products were targeted in this terrible situation. They then ran away from this chaotic condition bringing their sugar industry skills and this fact led the sugar industries to spread out of Batavia around Java. Batavia, which was initially as the sugar industry basis, therefore,ÃÂ was not surrounded by cane plantations; meanwhile, these types of plantations were spreading in the north coastline of Java and some parts of Central Java and East Java remote areas became sugar industry centers and the people of each area, therefore, were developing. Key words: Chinese Ethnic, Chaos,ÃÂ Batavia, Sugar.ÃÂ Kerusuhan rasial yang terjadi di Batavia pada tahun 1740 memiliki dampak yang luar biasa bagi perkembangan sosio-ekonomi Jawa secara umum. Etnis Cina yang menjadi sasaran dalam peristiwa tersebut ternyata sebagian merupakan pemilik industri gula yang menguasai ja-ringan sejak hulu hingga hilir. Ketika kemudian mereka melarikan diri ke luar kota Batavia, mereka membawa keahlian mereka dalam industri gula dan dengan demikian industri gula menyebar ke seluruh Jawa. Batavia yang semula menjadi perintis industri gula tidak lagi dikelilingi oleh perkebunan-perkebunan tebu sementara daerah pantai utara Jawa dan sebagian peda-laman Jawa Tengah dan Jawa Timur berkembang menjadi pusat industri gula dengan perkembangan masyarakatnya masing-masing. Kata kunci: etnis Cina, Kerusuhan, Batavia, Gula. ÃÂ ÃÂ